TREND SEGMENTASI PASAR OBJEK WISATA SIGARAN JIWA DI KAMPUNG JAYAPURA KECAMATAN BUNGARAYA KABUPATEN SIAK PADA MASA PANDEMI COVID-19 - Khafizah "; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The study was to find out the market rate of the Sigaran Jiwa tourist attractions of the covid pandemic 19. The research is located in Jayapura Village, Bungaraya Sub-District, Siak district. The kind of research was used of quantitative descriptive, with a sample of 100 respondents, data collection techniques using a questionnaire measured to the likert scale, observation, documentation and literature study. Data analysis used of descriptive and cluster analysis. A descriptive analysis of the distribution of the frequency of dominant respondents visited during the covid-19 pandemic. The cluster analysis had been obtained with four groups. If by psychographic terms the allocentris, the mid-centris, whereas by behavior the group is based on personal experience and social media.and the dominan segments is the type of mid-centris Keywords: Market Segmentation, Sigaran Jiwa , The Pandemic Covid-19